Analisis SWOT pada Usaha Mikro, Kecil dan Menengah (Studi Kasus pada Waroeng Sembako Budhe) - Dzakiyyah, Nuha; Daspar, Daspar (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
MSMEs have an important role in the Indonesian economy, but often face challenges due to changes in the business environment. This research aims to analyze the Strengths, Weaknesses, opportunities, and threats (SWOT) of Waroeng Sembako Budhe as a basis for preparing business development strategies. The method used is qualitative case study, with observation, interview, and documentation techniques. The results show that the shop has Strengths such as varied products, strategic location, affordable prices, and loyal customers. Weaknesses found include the absence of digital records, limited promotion, and manual stock management. Opportunities that can be utilized include online promotions, inter-SUMKM cooperation, and delivery services. Meanwhile, threats come from competition from modern minimarkets, price fluctuations, and shifting shopping patterns. The suggested strategy is to utilize Strengths to capture opportunities and overcome Weaknesses with external support.